Cardiopulmonary exercise testing: arm crank vs cycle ergometry. (10th April 2013) - Orr, J. L.; Williamson, P.; Anderson, W.; Ross, R.; McCafferty, S.; Fettes, P.
Summary This pilot study compared oxygen consumption during arm crank and cycle ergometer tests in 15 women. The mean (SD) peak oxygen consumption was less with arm cranking (25 (5) ml.kg−1.min−1) than with cycling (40 (7) ml.kg−1.min−1), p < 0.0001. The mean (SD) anaerobic threshold was less with arm cranking (13 (2) ml.kg−1.min−1) than with cycling (20 (4) ml.kg−1.min−1), p < 0.0001. There was moderate correlation, r2 = 0.60, between the anaerobic thresholds determined by arm and leg exercise, p = 0.0007. This study suggests that arm crank cardiopulmonary exercise testing could be used for pre‐operative assessment in those unable to cycle.